Low‐Energy Pathways Found for the NH3 Activation and H2 Elimination by the Werner‐Type Complexes M(NH3)4+ (M=Fe, Ru and Os). Issue 47 (17th December 2020) - Avilés, Alejandro; Torres, Ana E.; Colmenares, Fernando
Abstract: The interactions of NH3 with the transition metal complexes M(NH3 )n + (M=Fe, Ru, Os; n=0−4) were investigated theoretically with the aim of analyzing the factors that determine their reactivity patterns and product distributions. The reactions of ammonia with the low‐coordination complexes of the three metallic ions (n=1−3) lead only to the addition product M(NH3 )n+1 + . However, once the highest‐coordinated complex M(NH3 )4 + is reached, each of the reactions evolves to metal‐inserted species through low energy channels. For osmium, the hydrogen abstraction from an additional NH3 molecule by the inserted intermediate H−Os(NH3 )4 ‐NH2 + leads to H2 elimination products along a favorable pathway. The facile breaking of the strong N−H bond of ammonia by these Werner‐type complexes is by far the most striking finding emerging from this study. Hopefully, this could inspire future contributions in the areas of chemical and bioinorganic catalysis. Abstract : The reactions of ammonia with the ammine complexes Fe(NH3 )3 +, Ru(NH3 )4 + and Os(NH3 )4 + evolve to metal‐inserted species along favorable energetic channels. The metal‐ligand interactions determine the energy profiles and the reactivity patterns followed by these reactions.